A investigação criminal e a vedação ao anonimato no sistema jurídico brasileiro - Souza, Rodrigo Telles de (2012)
The thesis, prepared with basis on deductive reasoning (through the utilization of general concepts of the fundamental rights theory) and on inductive logic (by means of the consideration of particular situations in which the theme has been approached) deals with the criminal investigation and the prohibition of anonymity in the Brazilian law system. The state criminal investigation activity presents not only a substantial constitutional basis, due to the objective dimension of fundamental rights (which imposes an obligation to protect these essential values), but also a formal constitutional basis, arising from the administrative principles of rule of law, morality and efficiency, referred to in article 37 of the Constitution. The criminal investigation, however, is not an unlimited pursuit, being restrained by the duty to consider fundamental rights that oppose to its realization. One of the limits of the state investigation activity, in the Brazilian law system, is the prohibition of anonymity, referred to in article 5°, IV, of the Constitution. This prohibition is a direct constitutional restriction to the freedom of expression that aims to ensure the credibility of the diffusion of ideas and prevent the abusive exercise of this fundamental right, which could harm both persons and the state, with no possibility of punishment to the offending party. Generally, based on this prohibition, it is affirmed that a criminal investigation cannot begin and progress founded on anonymous communication of crimes. Informations about crimes to the investigative authorities require the correct identification of the stakeholders. Therefore, it is sustained that the prohibition of anonymity also comprehends the prohibition of utilization of pseudonyms and heteronyms. The main purpose of this essay is to recognize the limits and possibilities in starting and conducting criminal investigations based on communication of crimes made by unidentified persons, behind the veil of anonymity or hidden by pseudonyms or heteronyms. Although the prohibition of article 5°, IV, of the Constitution is not submitted to direct or indirect constitutional restrictions, this impediment can be object of mitigation in certain cases, in attention to the constitutional values that support state investigation. The pertinence analysis of the restrictions to the constitutional anonymity prohibition must consider the proportionality, integrated by the partial elements of adequacy, necessity and strict sense proportionality. The criminal investigation is a means to achieve a purpose, the protection of fundamental rights, because the disclosure of facts, through the investigatory activity, gives rise to the accomplishment of measures in order to prevent or punish the violations eventually verified. So, the start and the development of the state criminal investigation activity, based on a crime communication carried out by an unidentified person, will depend on the demonstration that the setting up and continuity of an investigation procedure, in each case, are an adequate, necessary and (in a strict sense) proportional means to the protection of fundamental rights